Effect of Splinting Health Education with Audiovisual Media on The Knowledge Level of Splinting in Students of Public Senior High School 1 Jember - Baskoro Setioputro; Azhar Mintarum; Siswoyo (Nursing and Health Sciences Journal (NHSJ), 2022)
The World Health Organization (WHO) states that the condition of traffic accidents in Indonesia is the third highest killer after coronary heart disease and tuberculosis, where this case is estimated to occur in 70% of students. Fractures are potential and actual threats that cause physiological and psychological disorders to a person's pain response. This study aimed to determine the effect of health education in splinting on the level of knowledge by using audiovisual media. The research design used a quasi-experimental method (quasi-experimental) with a non-equivalent control group approach. The sampling technique is simple random sampling, and the number of samples used is 51 respondents. The research instrument used a knowledge-level questionnaire on splinting and audiovisual media. The Wilcoxon sign test and Mann-Whitney analyzed data. The Wilcoxon analysis showed that the p-value in the intervention group was 0.005 < 0.05. And in the control group, the p-value was 0.014 < 0.05. While according to the Mann-Whitney test, the p-value was 0.000 < 0.05, it can be concluded that there is an effect of health education splinting with audiovisual media on the knowledge level of splinting in public senior high school students. The use of video for education is very effective in changing individual knowledge and behaviour. Providing education through videos will make it easier to convey information and facilitate behaviour change. Besides, videos can increase self-confidence and confidence about the educational material delivered.